Low depression scores among pet dog owners – a comparative cross-sectional study from Anuradhapura Sri Lanka - Rathish, Devarajan; Rajapakse, Jayanthe; Weerakoon, Kosala (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The role of canine companionship in psychosocial and cardiovascular health is increasingly explored. However, such studies are scarce in South Asia. Hence, we aim to compare psychosocial and cardiovascular indices between pet dog owners and age and sex-matched non-pet owners in Anuradhapura, Sri Lanka. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A community-based, comparative, cross-sectional study was done among 52 pet dog owners and 52 age, sex-matched non-pet owners. An allostatic load was calculated using predefined cutoffs. Chi-square (or Fisher’s exact), Mann Whitney U, and Spearman’s rho were performed (p<0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The pet dog owners’ group had a significantly lower mean (SD) [7.8 (7.2)], and median (interquartile range) [6 (2–12.5)] depression score when compared to the non-pet owners [11.2 (8.6)], 10 (6–14.5) respectively (p=0.03). Also, the pet dog owners showed a significant negative correlation between the pet bond scale score and cortisol (r=-0.36, p=0.01). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. A significantly lower depression score in the pet dog owners’ group than in the non-pet owners’ group was observed. And, the pet bond score had a significant negative correlation with the stress hormone cortisol. Thus, pet dog ownership could improve psychosocial health and will guide towards one-health interventions and research among South Asian communities.